Use of Acoustic Emission for the Detection of Brittle Rock Failure under Various Loading Rates. (8th March 2018) - Shuang, Hai-qing; Li, Shu-gang; Liu, Lang; Chen, Gao-feng; Song, Ki-Il
Abstract : Acoustic emission has a direct correspondence to the internal damage of a material. To determine the effects of the loading rate on the mechanical properties of rock, the initial damage was characterized using the acoustic emission technique when a uniaxial preloading was imposed on a cylindrical rock sample. On this basis, the uniaxial compression test was conducted on sandstone that contains initial damage induced under a range of loading rates. The effects of the initial damage and loading rate on the mechanical properties of rock were analyzed. The uniaxial preloading generated randomly distributed microcracks in the natural rock. The results showed that the acoustic emission and positioning technique can characterize accurately the damage and its position due to preloading. The development of microcracks was found to be strongly dependent on the loading rate. Moreover, the loading rate accelerated the degradation of the rock strength. The effects of the loading rate and initial damage on the mechanical properties of rock are a complicated coupled process. From the experimental test result, a constitutive equation was constructed based on the damage mechanics.